Study the Effect of Anastrozole on Estradiol and Cytochrome P450 (Aromatase Enzyme) in Postmenopausal Breast Cancer Patients. - Abd-Allateef, Mays Waad; Hassan, Firas Abd-Alla; Saleh, Wieeam Abdulfatta (Al-Nahrain Journal of Science, 2018)
In this study sixty patients were selected according to a positive estrogen receptor. All of 60 naturally or surgically postmenopausal women that had a diagnosis of breast cancer verified by histology breast cancer. Subdivided to with hormone treatment or without any treatment, Forty patients (group P1) with the ages range from 46 to 75 years, and were being treated with an aromatase inhibitor, Arimidex (1 mg) once daily, and another twenty (group P2) as newly diagnosed of breast cancer with ages ranging from 47 to 75 years. While the age of control ranging from (48-75) years old, used as a reference. Recent investigations have challenged the hypothesis that aromatization of androgens into estrogen is the sole production pathway for estrogens in postmenopausal women. The finding that estradiol persists in the plasma of patients receiving anastrozole treatment despite a near total inhibition of the aromatase enzyme suggests that alternative pathways for estrogen synthesis exist, which appeared in our results, aromatase and estradiol with treatment (452.34pg/ml) and (13.09pg/ml) respectively. An although evidence a positive and strong correlation between aromatase enzyme and estradiol (r=0.573, P=0.00).